Microbial and nutritional regulation of high-solids anaerobic mono-digestion of fruit and vegetable wastes. Issue 4 (16th February 2018) - Mu, Hui; Li, Yan; Zhao, Yuxiao; Zhang, Xiaodong; Hua, Dongliang; Xu, Haipeng; Jin, Fuqiang
ABSTRACT: The anaerobic digestion of single fruit and vegetable wastes (FVW) can be easily interrupted by rapid acidogenesis and inhibition of methanogen, and the digestion system tends to be particularly unstable at high solid content. In this study, the anaerobic digestion of FVW in batch experiments under mesophilic condition at a high solid concentration of 10% was successfully conducted to overcome the acidogenesis problem through several modifications. Firstly, compared with the conventional anaerobic sludge (CAS), the acclimated anaerobic granular sludge (AGS) was found to be a better inoculum due to its higher Archaea abundance. Secondly, waste activated sludge (WAS) was chosen to co-digest with FVW, because WAS had abundant proteins that could generate intermediate ammonium. The ammonium could neutralize the accumulated volatile fatty acids (VFAs) and prevent the pH value of the digestion system from rapidly decreasing. Co-digestion of FVW and WAS with TS ratio of 60:40 gave the highest biogas yield of 562 mL/g-VS and the highest methane yield of 362 mL/g-VS. Key parameters in the digestion process, including VFAs concentration, pH, enzyme activity, and microbial activity, were also examined.